Heat transfer intensification induced by electrically generated convection between two elliptical cylinders - Elkhazen, Mohamed Issam; Hassen, Walid; Kolsi, Lioua; Öztop, Hakan Fehmi; Al-Rashed, Abdullah A. A. A.; Borjini, Mohamed Naceur; Abu-Hamdeh, Nidal (Elsevier France-Editions Scientifiques Medicales Elsevier, 2019)
A computational study has been performed to see the heat transfer intensification induced by electrically generated convection in a two co-focal elliptical cylinder layers for dielectric liquid. Temperature of the inner cylinder is higher than of outer one. Finite volume method is used to solve the governing equations by writing a homemade computer code. The study is performed for dimensionless electric Rayleigh number (0 <= T <= 700), Rayleigh numbers (10(2) <= Ra <= 10(5)), eccentricity ratio (0.4 <= e <= 1). It is observed that the unipolar charge injection by the internal electrode changes significantly the topology of the fluid flow. Moreover, the computations highlight an important effect of the eccentricity value on the intensity and circulation cell number. Finally, it is found that heat transfer is improved with increasing dimensionless electric Rayleigh number.
Keywords: Dielectric liquid; Elliptic cylinders; Electro-thermo-convection